Refusal of male partner responsibility and pregnancy support: prevalence, associated factors and health outcomes in a cross sectional study in Harare, Zimbabwe - Simukai Shamu; Patience Shamu; Mercilene Tanyaradzwa Machisa (BMC Public Health)
Abstract Background The phenomenon of fathers refusing responsibility during pregnancy has not received adequate attention in African studies. This paper assesses associated factors and pregnancy-related outcomes when fathers refuse to support partners’ pregnancies and undertake parental responsibilities. Methods A cross-sectional survey of 15–49-year-old postnatal (1–6 weeks) women was conducted at six urban health facilities in Harare. Participants were interviewed about their male partners’ refusal to support their pregnancies and parenting, bride price payments (indicating marriage commitment), partner violence and control, alcohol abuse and family planning decision-making. Pregnancy health outcome data including antenatal care attendance, low birth weight (LBW)(< 2500 g) and postnatal depression were collected through interviews and clinic records. Multiple regression models were built to assess gender-related factors and health outcomes associated with male partners’ refusal of parenting responsibilities. Results Of the 2042 women interviewed, 6.4% reported partner refusal to support the pregnancy or parenting. Higher odds of partner refusal of fathering responsibility were associated with partners not paying bride price (aOR 9.31; 95% CI 1.16–74.59), violence perpetration during pregnancy (aOR 2.84; 1.28–6.23), highly controlling behaviours (aOR 4.96; 2.83–8.69), alcohol abuse (aOR 1.78; 1.05–3.02), unintended pregnancy (aOR 3.72; 1.84–7.53) and partner refusal to use contraceptives (aOR 3.64; 1.86–7.14). Women who used contraceptives (aOR 0.40; 0.23–0.71), made joint (aOR 0.30; 0.14–0.67) or individual (aOR 0.25; 0.07–0.94) pregnancy decisions were protected from partner refusal of parenting responsibility. Women’s depressive symptomatology (aOR2.64; 1.52–4.59), LBW (aOR5.30; 1.18–23.74) and partner discouragement of antenatal care attendance (aOR 3.86; 1.13–13.17) were pregnancy outcomes associated with partner refusal of parenting responsibility. Conclusions Male partners’ refusal to acknowledge parenting responsibility was associated with men’s abusiveness, absence of commitment to long-term relationship/marriage, gender unequal practices and negative maternal and child health outcomes. Parenting programmes must be instituted and prioritise transforming traditional gender norms to improve fathering responsibilities.